Antihyperglycaemic activity of alcoholic extract of Aerva lanata (L.) A. L. Juss. Ex J. A. Schultes leaves in alloxan induced diabetic mice - Deshmukh, Tushar A; Yadav, Bapuso V; Badole, Sachin L; Bodhankar, Subhash L; Dhaneshwar, Sunil R (Journal of Applied Biomedicine, 2008)
Aerva lanata known as Polpala, is prostrate or decumbent to erect herb. The objective of the present investigation was to study the antihyperglycaemic activity of alcoholic extract of Aerva lanata (called AL-alc) leaves on serum glucose levels, and on the oral glucose tolerance test (OGTT) in alloxan induced diabetic mice. AL-alc (100, 200 and 400 mg/kg) and glyburide (10 mg/kg) were administered orally in alloxan (70 mg/kg, i.v.) induced diabetic mice. In the acute study, the serum glucose level was estimated at 0,2,4,6 and 24 h after the administration of the drug. The subacute study involved repeated administration of the drugs for 28 days and then a rest period of 7 days, serum glucose level estimation at 7, 14, 21, 28 and 35 days by the glucose oxidase / peroxidase method and the recording of the body weights of the mice. In the oral glucose tolerance test (OGTT), D-glucose (2.5 g/kg) was administered to nondiabetic and diabetic mice half an hour after pretreatment with AL-alc (100, 200 and 400 mg/kg) and glyburide (10 mg/kg). Serum glucose levels were estimated 30 min prior to glucose administration and at 0, 30, 60 and 120 min after glucose loading. In AL-alc (400 mg/kg), the onset was 4 h, the peak effect was 6 h but the effect waned at 24 h. In the subacute study, repeated administration (once a day for 28 days) of the glyburide and AL-alc caused a significant reduction in the serum glucose level as compared to the vehicle treated group. AL-alc (400 mg/kg) treatment prevented a decrease in the body weight of the diabetic mice. In the OGTT, AL-alc (400 mg/kg) increased the glucose threshold at 60 min after the administration of glucose. The AL-alc (400 mg/kg) showed significantly more antihyperglycaemic activity than AL-alc (100 and 200 mg/kg).
Keywords: Plant Extracts; rostlinné extrakty; Body Weight; alloxan; Alloxan; experimentální diabetes mellitus; Diabetes Mellitus, Experimental; Amaranthaceae; hypoglykemika; tělesná hmotnost; glukózový toleranční test; Blood Glucose; Glucose Tolerance Test; Mice; Hypoglycemic Agents; krevní glukóza; myši